Micromorphological Characterization of Some Volcanic Soil In West Java - Arifin, Mahfud; Devnita, Rina (Geological Agency, 2008)
http://dx.doi.org/10.17014/ijog.vol3no4.20082Micromorphological characterization has been studied on six pedons of soils developing in volcanic materials in West Java. The pedons represent deposits of different volcanoes (Mount Tangkuban Perahu, Mount Patuha and Mount Papandayan) with different ages (Pleistocene, Holocene) within two types of volcanisms (andesitic, basaltic), and three agroclimatic zones (A, B1, B2). Undisturbed soil samples were taken from each identifiable horizon for thin section preparations. Observations were carried out by means of a magnifying lens, binocular stereomicroscope, polarization microscope, and scanning electron microscope (SEM). The result demonstrates that micromorphological characteristics of volcanic soils developing from different ages, types of parent material, and climate were different through their c/f related distribution 2Âµ patterns, c/f ratios, sorting, infillings and coatings of voids, and microstructure. Â